What should we do about habitual caffeine use in athletes? - Pickering, C.; Kiely, J. (Sports Medicine, 2019)
Caffeine is a well-established ergogenic aid, demonstrated to enhance performance across a wide range of capacities through a variety of mechanisms. As such, it is frequently used by both athletes and non-athletes alike. As a result, caffeine ingestion is ubiquitous in modern society, with athletes typically being exposed to regular non-supplemental caffeine through a variety of sources. Previously, it has been suggested that regular caffeine use may lead to habituation and subsequently a reduction in the expected ergogenic effects, thereby blunting caffeine`s performance-enhancing impact during critical training and performance events. In order to mitigate this expected performance loss, some practitioners recommended a pre-competition withdrawal period to restore the optimal performance benefits of caffeine supplementation. However, at present the evidence base exploring both caffeine habituation and withdrawal strategies in athletes is surprisingly small. Accordingly, despite the prevalence of caffeine use within athletic populations, formulating evidence-led guidelines is difficult. Here, we review the available research regarding habitual caffeine use in athletes and seek to derive rational interpretations of what is currently known—and what else we need to know—regarding habitual caffeine use in athletes, and how athletes and performance staff may pragmatically approach these important, complex, and yet under-explored phenomena.